The SAGE handbook of qualitative geography - DeLyser, Dydia (SAGE, 2010)
Human geography has always been grounded in what we now recognize as qualitative methods - in techniques of visual assessment, archival research, participant observation interviewing, and so on. This handbook is a key research tool for both beginning and advanced practitioners.